With the benefit of hindsight: Valedictory reflections from departmental secretaries, 2004-11 - Wanna, John (ANU Press, 2012)
Secretaries of government departments in Australia are the bureaucratic leaders of their generation. They are ambitious, highly-talented executives who have risen to the very pinnacle of their chosen vocation - public service to the Australian nation - usually after having spent most, if not all, of their professional careers dedicated to the public service. They serve governments as their top advisers and in policy terms are often some of the most important decision-makers in the country. This collection brings together the valedictory speeches and essays from a departing group of secretaries (and one or two other equivalent agency heads) who left the Australian Public Service between 2004 and 2011. Over this period of time it gradually became accepted that departing secretaries and heads of significant agencies would present a valedictory address to their peers at a public farewell function. The first two speeches in this collection were initiated informally and given at functions organised by their agencies; in 2005 the process was formalised with the Australian Public Service Commission acting as organiser. These contributions contain reflections, commentaries, occasional fond memories or key turning-points in careers, critiques of changes that have occurred and an outline of the remaining challenges their successors will face as the public administrators of tomorrow. From the outset it is clear that there is no uniform message, no single narrative levelled either in praise or in criticism, other than pride in the public service and strong belief in the contribution it makes to the Australian community. They have their own personal 'takes' on how the public service looks to them, on its performance and on the challenges confronting public administration into the future. Most spend some time looking back, reflecting on the extent of change that has occurred over the length of their careers; but equally importantly they look forward, anticipating future policy dilemmas and capacity challenges.